Growth and Survival Performance of Transplanted Acropora Fragment in a Nursery Floating - Hamid; Lalu Samsul Rizal; Denianto Yoga Sativa (Jurnal Biologi Tropis, 2023)
The status of the condition of Indonesia's coral reefs is mostly categorized as moderate and damaged. Relatively inexpensive and easy-to-implement rehabilitation methods need to involve the participation of many stakeholders. The method of transplanting coral fragments by hanging (floating) from the surface of the water will be more efficient, especially in their maintenance. This study aims to investigate the most suitable water depth to support the growth and survival of the transplanted coral fragments. A non-factorial Completely Randomized Design (CRD) field experiment with 3 (three) treatments, namely different seedbed depths, 2 m, 4 m, and 6 m respectively. Each treatment was repeated 4 (four) times. The results of analysis of variance showed that the absolute growth rate of coral fragments transplanted by hanging from the surface of the water at different depths (2 m, 4 m, 6 m) showed no significant difference (P-value > 0.05). This shows that the environmental conditions at a depth of 2 m-6 m are relatively the same, so that on average all coral fragments have almost the same growth potential (0.29 cm/month). Meanwhile, the survival rate obtained is also very high (> 90%). These results confirm that the method of transplanting corals by hanging from the sea surface is technically feasible and gives good results. This will help many stakeholders to be involved in optimizing the economic potential value of coral reefs, as well as increasing participation in the conservation and rehabilitation of coral reefs.